Estimating Unsaturated Hydraulic Functions for Coarse Sediment from a Field‐Scale Infiltration Experiment. Issue 3 (13th March 2014) - Thoma, Michael J.; Barrash, Warren; Cardiff, Michael; Bradford, John; Mead, Jodi
Abstract : Conglomeratic alluvial sediments (sand–gravel–cobbles) are common in fluvial, periglacial, and tectonically active regions but have received little attention with respect to unsaturated flow, specifically moisture–tension–conductivity relationships, due to difficulty in making measurements in the field or laboratory and lack of agricultural value. We used a field‐scale infiltration experiment, a one‐dimensional layered forward model, and parameter estimation modeling to examine in situ flow behavior between residual and partial saturation in a four‐layer system under steady infiltration (0.84 cm h −1 ) for 19 h. Prior information from ground‐penetrating radar, grain‐size distributions from core samples, and long‐term tension (ψ) and moisture (θ) monitoring were used to define geologic structure, simulate test behavior, and provide initial parameter estimates. Vertically distributed measurements of ψ( t ) and θ( t ) from the experiment were matched using four parameters (θs, α, n, and K s ) of the van Genuchten–Mualem (VGM) relationships for each material layer and a Metropolis–Hastings (MH) search with multiple, independent‐chain runs to 10 6 samples each. Scale reduction factors indicated convergence of independent chains for 11 of 16 parameters. Final distributions of individual parameters varied from normal to nearly uniform distributions, and some parameter pairs showed high cross‐correlation ( R 2 > 0.9). Results showed that (i) VGM relationships can be applied to these coarse, conglomeratic soils to characterize unsaturated flow behavior across the natural range of partial saturation, (ii) even under high sustained infiltration rates, these coarse conglomeratic soils remain well drained, despite relatively low porosity and significant cobble fraction, and (iii) high uncertainty and nonconvergence of MH chains does not lead to significant misfit of the observed data. These findings imply that a significant cobble fraction does not markedly reduce infiltration at low saturation levels that develop under natural recharge conditions.